Ammonia line strengths and N2-, O2-, Ar-, He-, and self-broadening coefficients in the v2 band near 10.4 µm. (March 2021) - Alturaifi, Sulaiman A.; Petersen, Eric L.
Highlights: Ammonia line strength measurements in the v 2 fundamental band near 10.4 µm. NH3 broadening coefficient measurements due to collisions of N2, O2, Ar, He, and NH3 . Measurements of the temperature-dependence of broadening coefficients up to 1800 K. Abstract: Scanning-wavelength laser absorption measurements were carried out to determine the line strengths and broadening coefficients due to collisions of N2, O2, Ar, He, and NH3 for 12 ammonia transitions in the Q-branch of the v 2 fundamental band near 10.4 µm. The measurements were conducted at 296 K using a high-resolution quantum cascade laser and span the frequency range of 957.5–963.0 cm −1 . The absorption features were fitted with a Voigt profile to obtain the spectroscopic parameters. The temperature-dependence of the Ar-broadening coefficients for two transitions, suitable for high-temperature NH3 detection, were measured using a shock tube for the temperature range of 921–1767 K. The reported spectroscopic parameters are useful for developing NH3 detection sensors, especially for high-temperature applications involving chemical reactions.